Methane potential from the digestion of food waste in a batch reactor - Seswoya, Roslinda; Abdul Karim, Ahmad Tarmizi; Darnak, Nur Aiza; Abd Rahman, Muhammad Fahmi (Science Publishing Corporation, 2018)
The anaerobic digestibility of a targeted substrate, measured as methane yield is conducted via biochemical methane potential (BMP). In this study, the batch BMP test was conducted using Automatic Methane Potential Test System (AMPTS II) for 25 days and focused on the methane production from the digestion of food waste (FW, in the form of raw and diluted) at inoculum to substrate ratio (I/S) ratio of 2:0 and under mesophilic temperature. The results showed that solids (TS and VS) concentration reduced significantly due to the dilution. The ultimate methane yields from the digestion of raw FW and diluted FW were 1891.91ml CH4/gVS and 1983.96 ml CH4/gVS respectively. This showed that the dilution significantly improved the methane yield. In addition, the lag phase of the methane yield curve for both BMP tests was less than one (1) day, showing the good biodegradability of FW. The kinetic methane production from laboratory data and Modified Gompertz modelling fitted well. However, the kinetic equation parameters such as Mo, Rm and  from the model were slightly lower based on the observation of the laboratory data.